Novel amino glycerin decorated ammonium polyphosphate for the highly-efficient intumescent flame retardance of wood flour/polypropylene composite via simultaneous interfacial and bulk charring. (1st September 2019) - Xu, Bo-Ren; Deng, Cong; Li, Ying-Ming; Lu, Peng; Zhao, Pan-Pan; Wang, Yu-Zhong
Abstract: Wood flour (WF) filled polymer composites are widely used in our daily life. Unfortunately, a wick effect of WF during burning seriously deteriorates the flame retardancy of wood-plastic composites. Traditional flame retardants cannot efficiently restrict the wick effect of WF due to their random distribution. In this work, amino glycerin decorated ammonium polyphosphate (APD-APP) was well designed and prepared through an ion exchange reaction to tailor the dispersion of flame retardant in WF-filled polymer composites. When the APD-APP was incorporated into the WF/polypropylene composite (WPC), it showed significantly different distribution compared to that of APP and mainly accumulated at the surface of WF, and then resulted in the formation of core-shell WF@APD-APP. More importantly, the flame retardancy of WPC/APD-APP is remarkably superior to that of WPC/APP. In vertical burning test, 25.0 wt% of APD-APP upgraded the UL-94 rating and limiting oxygen index (LOI) of WPC from no rating and 19.0% to the corresponding V-0 rating and 29.0%. Moreover, the melt dripping of WPC was completely eliminated by APD-APP. In the combustion test, the peak of heat release rate and total smoke production for WPC were respectively decreased by 70.0% and 76.6% in the presence of 30.0 wt% of APD-APP. In addition, mechanical properties of WPC/APD-APP are also superior to that of WPC/APP. The mechanism for the excellent flame retardancy of WPC/APD-APP revealed that the formed core-shell WF@APD-APP affected a residual network through the intergrowth charring of APD-APP and WF during thermally decomposing, and then the wick effect of WF was significantly weakened. Finally, the flame retardancy of WPC/APD-APP was enhanced through typical intumescent flame-retarding action via simultaneous interfacial and bulk charring.